The basics of foreign exchange markets : a monetary systems approach - Gerdes, William D. (2014 digital library., 2015)
Foreign exchange markets are inextricably entwined with underlying monetary standards. Thus, they are treated conjointly. Four different exchange rate regimes are analyzed: (1) foreign exchange markets with commodity money; (2) foreign exchange markets with fiduciary money; (3) foreign exchange markets with fiat money--fixed exchange rates; and, (4) foreign exchange markets with fiat money--flexible exchange rates. For the last eight decades, most countries have operated with fiat monies. For proponents of the fiat money standard, one of its desirable attributes is that it provides individual countries with considerable monetary autonomy. However, both analytics and experience indicate that this is not always the case. Whether a country has more monetary autonomy depends upon whether fiat money is paired with fixed exchange rates (regime 3) or flexible exchange rates (regime 4). More autonomy is possible with flexible exchange rates (regime 4). Such autonomy is largely possible because foreign exchange markets are allowed to accommodate the wide variations in national monetary policies. Under this regime, the purchasing power parity (PPP) theory of exchange rates assumes elevated importance in accounting for foreign exchange market adjustments. Exchange rate regime 4 has been in place (in many countries) for more than four decades, and there are critics. Those who advocate scrapping this arrangement generally favor a return to either regime 2 or regime 3.